THE EFFECT OF THE RATIO OF SHARING THICKNESS (λ) ON ROUNDING WITH TAPERED LATHE PROCESS ON ALUMUNIUM 6061 - Tomi Ari Setyanto (TRANSMISI, 2019)
This study aims to find the value of the L/D gradient ratio, the value of the compression ratio of thick thickness (λ) and roundness value. The method used in this study is an experiment with data collection on; spindle speed (n), cutting depth (a), angle (α), and tool corner radius (nsr) vary. The results achieved at an L/D ratio of 3.28, cutting depth (a) 0.6 mm, spindle rotation (n) 250 rpm, tool corner radius (nsr) 0.2 mm and a sharpness angle of 2.5˚ experienced compression ratio the largest thick thickness (λ) is 2.53, while at the 2.62 L/D ratio, the cutting depth (a) 0.2 mm, spindle rotation (n) 500 rpm, tool corner radius (nsr) 0.2 mm and the steepness angle of 2.5˚ experiences the lowest compression ratio of thick thickness (λ) of 0.53. With a large compression ratio of thick fur (λ) the roundness value will also be large, in the compression ratio of thick thickness (λ) 2.53 get a roundness value of 1.3 µm. While the lowest roundness value of 0.5 μm occurs in the compression ratio of thick thickness (λ) 0.53.